REALIZATION OF TOTAL HARMONIC DISTORTION MEASUREMENT OF ACOUSTIC SOURCE SIGNAL SYSTEM FOR FREQUENCY OF 125 HZ AND 1000 HZ - Bondan Dwisetyo; Denny Hermawanto; Dodi Rusjadi; Chery Chaen Putri; Maharani Ratna Palupi; Fajar Budi Utomo (Badan Standardisasi Nasional, 2019)
The measurement of total harmonic distortion (THD) of an acoustic source signal system has carried out in Laboratory Acoustics and Vibration, Sub-directorate of National Measurement Standards for Acoustics and Vibration - BSN. The aim of this research is, therefore, to measure and analize the THD values that produced by the system that consists of a signal generator, a power amplifier, and a passive loudspeaker with fundamental frequencies of 125 Hz and 1000 Hz. This measurement should be implemented because it has never been performed in this laboratory. Moreover, this system always be used for either calibration or measurement of acoustical instruments such as sound level meter and noise dosimeter. The method used to measure THD is a free field method using a full anechoic chamber with narrow band analysis. Measurand to determine THD is sound pressure level (SPL) with output of loudspeaker are 94 dB, 104 dB, and 114 dB. From result of measurement was found THD value of fundamental frequencies of 125 Hz and 1000 Hz. For the former frequency, the maximum THD was found at SPL of 94 dB where its value was 1,86 %. Meanwhile the later, the maximum value of THD was 1,94 % also at SPL 94 of dB. The results of this measurement can be used into uncertainty budget for either calibration or testing of acoustical instruments, and also support for validation of calibration of noise dosimeter based on percentage of noise exposure dose using acoustic comparison coupler that still under research and development in this year.